Mechanical evaluation of four narrow-diameter implant systems - Hirata, Ronaldo; Bonfante, Estevam A.; Machado, Lucas S. [UNESP]; Tovar, Nick; Coelho, Paulo G. (Quintessence Publishing, 2014)
Purpose: This study aimed to evaluate the survival probability of four narrow-diameter implant systems when subjected to fatigue loading. Materials and Methods: Seventytwo narrow-diameter implants to be restored with single-unit crowns were divided into four groups (n = 18): Astra Tech (3.5-mm diameter), with a standard connection (ASC); BioHorizon (3.4-mm diameter), with a standard connection (BSC); Intra-Lock (3.4-mm diameter), with a standard multilobular connection (ISC); and Intra-Lock (3.4-diameter), with a modified square connection (IMC). The corresponding abutments were screwed onto the implants, and standardized metal crowns (maxillary central incisors) were cemented and subjected to step-stress accelerated life testing in water. Use-level probability Weibull curves and reliability for 100,000 cycles at 150 and 200 N (90% two-sided confidence intervals) were calculated. Polarized light and scanning electron microscopes were used to access the failure modes. Results: The calculated survival probability for 100,000 cycles at 150 N was approximately 93% in group ASC, 98% in group BSC, 94% in group ISC, and 99% in group IMC. At 200 N, the survival rate was estimated to be approximately < 0.1% for ASC, 77% for BSC, 34% for ISC, and 93% for IMC. Abutment screw fracture was the main failure mode for all groups. Conclusions: Although the probability of survival was not significantly different among systems at a load of 150 N, a significant decrease was observed at 200 N for all groups except IMC.